An Umbrella Review of Systematic Reviews and Meta-Analyses Evaluating the Success Rate of Prosthetic Restorations on Endodontically Treated Teeth - Amirhossein Fathi; Behnaz Ebadian; Sara Nasrollahi Dezaki; Nahal Mardasi; Ramin Mosharraf; Sabire Isler; Shiva Sadat Tabatabaei (International Journal of Dentistry, 2022)
Statement of the Problem. Various direct and prosthetic restorations are clinically used to restore endodontically treated teeth. However, determining the most successful and reliable treatment to restore endodontically treated teeth is affected by numerous elements and still unclear for most clinicians. Therefore, this umbrella review study assessed the systematic/meta-analytic reviews (S/M-R) regarding the success rate of prosthetic restorations in endodontically treated teeth. Materials and Methods. The electronic search was conducted in the MEDLINE/PubMed, Cochrane, and Google Scholar databases until November 2020, regardless of language limitations. The inclusion criterion was as follows: S/M-R regarding prosthetic restorations in endodontically treated teeth. Three qualified researchers evaluated the inclusion criteria and bias risk. The fourth investigator was referred to when facing any doubtfulness. Results. From 43 achieved S/M-R, 14 studies were selected for this inquiry. Primary extracted information included success rate, survival rate, and postendodontic failure rate. Five S/M-R had a moderate risk of bias, and nine S/M-R had a low risk of bias and were considered strong clinical evidence in this examination. According to the low-risk reports, the success rate of fiber posts was higher than that of metal posts; the rate of root fracture in metallic and fiber posts was alike; the failure rate for fiber posts was comparable to fixed partial dentures or single crowns; the construction of endocrowns was likely to perform better than intracanal posts, composite resin, or inlay/onlay restorations. Conclusion. It appears that with practice and experience, deciding which type of restoration to choose changes. In dental restorations associated with root canal therapy, the single crowns are likely to be a proper option. Nevertheless, due to the heterogeneity of the studies, more clinical assessments are required to achieve more specific findings in this field.